Intravenous AAV9 administration results in safe and widespread distribution of transgene in the brain of mini-pig - Lin, Yingqi; Li, Caijuan; Wang, Wei; Li, Jiawei; Huang, Chunhui; Zheng, Xiao; Liu, Zhaoming; Song, Xichen; Chen, Yizhi; Gao, Jiale; Wu, Jianhao; Wu, Jiaxi; et al. (Frontiers in Cell and Developmental Biology, 2023)
Animal models are important for understanding the pathogenesis of human diseases and for developing and testing new drugs. Pigs have been widely used in the research on the cardiovascular, skin barrier, gastrointestinal, and central nervous systems as well as organ transplantation. Recently, pigs also become an attractive large animal model for the study of neurodegenerative diseases because their brains are very similar to human brains in terms of mass, gully pattern, vascularization, and the proportions of the gray and white matters. Although adeno-associated virus type 9 (AAV9) has been widely used to deliver transgenes in the brain, its utilization in large animal models remains to be fully characterized. Here, we report that intravenous injection of AAV9-GFP can lead to widespread expression of transgene in various organs in the pig. Importantly, GFP was highly expressed in various brain regions, especially the striatum, cortex, cerebellum, hippocampus, without detectable inflammatory responses. These results suggest that intravenous AAV9 administration can be used to establish large animal models of neurodegenerative diseases caused by gene mutations and to treat these animal models as well.